Flying blind with badly behaving technology: a case study of integrating 1:1 computers in middle school - Richmond, Gary (Kansas State University, 2018)
Information and communication technology is becoming more affordable and available to schools. In response to the emerging need to produce students with academic skills appropriate for 21st-century learners, many schools are investing large sums of money into this technology in an effort to create learning environments where students have a 1:1 ratio with access to tools such as laptops, tablets, or other types of portable devices. While there is evidence demonstrating that 1:1 student device adoptions can influence instruction and student learning, there is an ever-present, evolving need for scholarship concerning the experiences of teachers participating in such initiatives. The premise of this study is that teachers can provide valuable understanding concerning 1:1 computer adoptions, as they are one of the primary instruments in its success. The purpose of this study was to explore how two middle school teachers in a Midwestern city described the effects of ubiquitous computer access for students on their instructional practices and overall student learning as they participated in a district-wide 1:1 computer initiative. Participants for this qualitative case study were selected through purposeful- and criterion-based sampling. The participants were chosen from a pool of classroom teachers participating in the early phase of their district’s 1:1 initiative. Additionally, the participants’ eagerness to participate in the study as well as their comfort level with technology played a role in selection. Symbolic interactionism provided the lens through which to analyze the participants’ meaning making and the framework of TPACK afforded the substantive lens for discussing their experiences. Many of the individual aspects of the findings of this study are not new or particularly insightful by themselves and largely confirm existing findings in the scholarship. However, the significance of this study lies not in the corroboration of existing scholarship, but instead in illustration of the anatomy of change. In the end, this study investigating ICT integration wasn’t about technology at all. It was about the experience of transition. This study, with rich detail and context, shows the anatomy of transition for the two participants’ pedagogical practices and beliefs from the start of the process to the end. It provides insight into how things come to be and the way in which they come to be. It provides insight into how and why participants moved back and forth across the TPACK domains as they assimilated their fundamental beliefs with their lived experiences. The outcomes of this research suggest avenues for policy makers, administrators, teachers, and professional development organizers to increase the influence of 1:1 initiatives. It is necessary for all involved stakeholders to understand the importance of professional development in affecting technology-related change and to include training in any 1:1 adoption plan. It is equally important for teachers to understand that they will need to leverage formal and informal avenues of professional development to further their professional learning. Professional development organizers need to be cognizant of the needs of the staff and provide targeted, content-specific training in a timely manner. Last, district and building leaders should be aware of their organizational culture and the underlying goals for their 1:1 initiative and keep these in mind as they lead their staff through the change process.
Keywords: TPACK; Educational technology integration